Alat Monitoring Detak Jantung dan Suhu Berbasis LoRa dan IoT Menggunakan Protokol MQTT - Sherli Tamara (Jurnal Teknologi Informasi dan Pendidikan, 2023)
Heart rate is one of the most important organs in the human body as it plays a role in the circulatory system. Body temperature is the result of the body's metabolic processes and is influenced by external and internal factors. In this research, we design a monitoring tool that uses LoRa and IoT technology to monitor heart rate and human body temperature. This tool aims to provide real-time health monitoring and can communicate remotely. MQTT allows efficient data transmission between connected devices in the network. Pulse heart rate sensor and temperature sensor MLX90614 The data obtained from these two sensors is sent through the LoRa network to the LoRa gateway. The LoRa gateway functions as a link between the monitoring device and the MQTT server. The gateway receives data from the monitoring device via the LoRa network and forwards it to the MQTT server via an internet connection. The MQTT server sends the data to an application that can be accessed via a smartphone. The test results show that the RSSI value of -72.5 dBm is obtained when the minimum distance is 5 metres. The lowest value for RSSI, which is -93.5 dBm, is obtained at the maximum testing distance of about 55 metres. For the results of the packet loss value is 0% occurs at a closer distance, but at a distance of 50m (5%) and at a distance of 55m (20%) indicates that the signal begins to weaken or experience interference at a greater distance